Outbreak Investigation of Cholera in Bharuch City - Navneet G. Padhiyar; Jivraj Damor (Medsci Publications, 2011)
Introduction: Cholera is an acute diarrheal disease, present in India since ancient times. Cholera epidemic was reported in June 2009 in Bharuch city, Gujarat. Aim: To find out the cause of cholera epidemic and to suggest preventive and control measure. Study design: Cross sectional study. Person from high-risk area were interviewed Results: Contamination of drinking water with sewage water was found to be the cause of this epidemic.